Caesarean myomectomy in a patient with multiple maternal and fetal comorbidities: a rare interesting case report - Pathan, Zeba H.; Chavan, Niranjan N.; Kampoowale, Shreya; Kapote, Deepali S.; Sakhalkar, Ashwini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Caesarean myomectomy has been traditionally discouraged due to the fear of complications like intractable haemorrhage, peripartum hysterectomy, and increased postoperative morbidity. Recently, a number of authors in their studies have shown that myomectomy during caesarean section does not increase the risk of haemorrhage or postoperative morbidity, if adequate haemostatic methods are used and done by skilled surgical hands. Caesarean myomectomy was performed in a case of elderly primigravida with 36-week gestation with chronic hypertension with polyhydramnios with anterior wall pedunculated fibroid of 8.6×7.2×8 cm and multiple small fibroids in the anterior wall, fundus and subserosal plane. Caesarean myomectomy is a safe and effective procedure in a tertiary care centre at hands of an experienced surgeon.